Advanced Multiphasing Switched-Capacitor DC-DC Converters : Pushing the Limits of Fully Integrated Power Management /: Pushing the Limits of Fully Integrated Power Management. (2020) - Butzen, Nicolas; Steyaert, Michiel
No abstract available